Ultrasound-Guided Breast-Conservative Surgery Decreases the Rate of Reoperations for Palpable Breast Cancer. Issue 6 (June 2018) - Vieni, Salvatore; Graceffa, Giuseppa; Priola, Roberta; Fricano, Martina; Latteri, Stefania; Latteri, Mario A.; Cipolla, Calogero
The purpose of this study is to verify whether the performance of ultrasound-guided quadrantectomy (USGQ) versus palpation-guided quadrantectomy (PGQ) can reduce the incidence of positive margins and if it can change the attitude of the surgeon. A retrospective study was conducted on 842 patients underwent quadrantectomy for breast cancer, 332 of them underwent USGQ, whereas 550 underwent PGQ. The histological type of the tumors and the margin status obtained with the histological examination were compared. The histological examination of the surgical specimen showed involvement of the margins in 24/842 patients (2.85%), 22 (2.61%) of them belonged to the PGQ group, and two to the USGQ group (P = 0.0011). The highest rate of microscopically positive margins was, statistically significant, for carcinoma in situ, when compared with patients with invasive carcinoma (0.0001). USGQ technique showed several advantages compared with PGQ. In fact, the former notes a lower positive margin rate and, consequently, a lower rate of reintervention. In addition, it may change the surgeon's attitude by causing him to remove another slice of margin to ensure more histological negativity. It should be the gold standard technique for breast-conservative surgery of palpable tumors.